IMPLEMENTASI WAKAF PRODUKTIF BERBASIS QA’IDAH DAR’ AL-MAFASID MUQADDAM ALA JALB AL-MASALIH: ANALISIS DIMENSI SYARIAH TERHADAP RISIKO PENGELOLAAN WAKAF - Imam Kamaluddin; Syamsuar, Mushaq (NATUJA: Jurnal Ekonomi Syariah, 2026)
The transformation of waqf into productive sectors introduces complex risk exposures that may lead to the loss of the principal asset (ḍayāʿ al-aṣl), directly contradicting the perpetual principle of taḥbīs al-aṣl. Existing literature is largely dominated by a benefit-maximization approach (jalb al-maṣāliḥ), thereby leaving a research gap in the form of a limited normative fiqh framework for risk prevention. To address this gap, this study aims to reconstruct risk management by positioning the legal maxim Dar’ al-Mafāsid Muqaddam ʿalā Jalb al-Maṣāliḥ as a foundation for substantive mitigation. Employing a normative legal research method with a juridical-normative approach, secondary data are analyzed through hermeneutic interpretation and synthesis. The findings reveal that the principle of preventing harm (dar’ al-mafāsid) necessitates prioritizing loss prevention over the pursuit of speculative benefits. Consequently, the application of this maxim demands a high standard of Sharīʿah prudentiality and significantly transforms the role of the nāẓir from a mere investment manager into a trustee. Overall, this study contributes theoretically by operationalizing a fiqh-based legal maxim to ensure prudence in the governance of productive waqf